Representasi Kemiskinan Dalam Film Parasite (Karya Boong Joon-Ho) - Muhamad Maruli Opradi; Susiyanto; M. Fikri Akbar (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study analyzes how the film Parasite depicts structural poverty through the denotative, connotative, and mythical meanings contained in each scene. At the denotative level, the film displays literal visual elements such as the Kim family's subterranean semi-basement, with dim, yellowish lighting, in stark contrast to the Park family's bright, modern, luxurious home. The connotative level reveals symbolic meanings where the semi-basement represents social decline and the vulnerability of the lower class, while the staircase motif connotes a metaphor for fragile social mobility and the cycle of poverty that is difficult to break. At the mythical level, the film dismantles capitalist ideology that naturalizes poverty as a "natural" consequence of social hierarchy. Using qualitative research methods and Roland Barthes' semiotic analysis techniques, researchers collected data through observation and documentation, and validated the data using triangulation. The results of the study using Roland Barthes' semiotic theory revealed that the visualization of poverty in the film clearly reflects structural poverty-a condition in which certain groups of people cannot access sources of income due to unfair social structures. This concept is reinforced by the Theory of Social Democracy which emphasizes that poverty is a systemic problem, not just the result of individual failure.